Design and Build a Web-Based E-Learning Application System at Paramarta Vocational High School - Iwan Giri Waluyo; Zulfikar Alwi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The conventional learning system is still being implemented at SMK Paramarta, which includes direct contact between teachers and students. However, with the advancement of technology, there is a need for an e-learning system that can facilitate the teaching and learning process and provide more varied learning activities for students. Therefore, this research aims to design and develop a web-based e-learning application system at SMK Paramarta. As a result, when a teacher is unable to attend, the teaching and learning process will be disrupted because there is no other media to deliver learning materials from the teacher to the students. The design of the Web-based E-learning Application System is built using HTML, JavaScript, PHP, MySQL, and CSS to beautify the e-learning pages that will be created. The web-based e-learning application system designed in this research can be an alternative modern and varied learning activity for students at SMK Paramarta. Additionally, this system can also assist teachers in providing learning materials and testing student understanding in a more effective and efficient manner. Therefore, it is hoped that the use of this system can improve the quality of education at SMK Paramarta. To ensure that the application runs smoothly, two testing phases are conducted: white-box testing and black-box testing on the data transfer process that runs within the e-learning application